Reengineering the Census Bureau's annual economic surveys - Abraham, Katharine G.; Citro, Constance F. (Constance Forbes), 1942-; White, Glenn D., Jr; Kirkendall, Nancy J. (Nancy Jean) (Consensus study report., 2018)
"The U.S. Census Bureau maintains an important portfolio of economic statistics programs, including quinquennial economic censuses, annual economic surveys, and quarterly and monthly indicator surveys. Government, corporate, and academic users rely on the data to understand the complexity and dynamism of the U.S. economy. Historically, the Bureau's economic statistics programs developed sector by sector (e.g., separate surveys of manufacturing, retail trade, and wholesale trade), and they continue to operate largely independently. Consequently, inconsistencies in questionnaire content, sample and survey design, and survey operations make the data not only more difficult to use, but also more costly to collect and process and more burdensome to the business community than they could be. This report reviews the Census Bureau's annual economic surveys. Specifically, it examines the design, operations, and products of 11 surveys and makes recommendations to enable them to better answer questions about the evolving economy"--Publisher's description